Hyperfine excitation of OH+ by H - Lique, Francois; Bulut, Niyazi; Roncero, Octavio (Oxford Univ Press, 2016)
The OH+ ions are widespread in the interstellar medium and play an important role in the interstellar chemistry as they act as precursors to the H2O molecule. Accurate determination of their abundance rely on their collisional rate coefficients with atomic hydrogen and electrons. In this paper, we derive OH+-H fine and hyperfine-resolved rate coefficients by extrapolating recent quantum wave packet calculations for the OH+ + H collisions, including inelastic and exchange processes. The extrapolation method used is based on the infinite order sudden approach. State-to-state rate coefficients between the first 22 fine levels and 43 hyperfine levels of OH+ were obtained for temperatures ranging from 10 to 1000 K. Fine structure-resolved rate coefficients present a strong propensity rule in favour of Delta j = Delta N transitions. The Delta j = Delta F propensity rule is observed for the hyperfine transitions. The new rate coefficients will help significantly in the interpretation of OH+ spectra from photon-dominated region (PDR), and enable the OH+ molecule to become a powerful astrophysical tool for studying the oxygen chemistry.
Keywords: molecular data; molecular processes; scattering